The thermal history of the intergalactic medium down to redshift z=1.5: a new curvature measurement - Boera, Elisa; Murphy, Michael T.; Becker, George D.; Bolton, James S. (Oxford University Press, 2014)
According to the photoheating model of the intergalactic medium (IGM), He ii reionization is expected to affect its thermal evolution. Evidence for additional energy injection into the IGM has been found at 3 ≲ z ≲ 4, though the evidence for the subsequent fall-off below z ∼ 2.8 is weaker and depends on the slope of the temperature–density relation, γ. Here we present, for the first time, an extension of the IGM temperature measurements down to the atmospheric cut-off of the H i Lyman-α (Lyα) forest at z ≃ 1.5. Applying the curvature method on a sample of 60 Ultraviolet and Visual Echelle Spectrograph (UVES) spectra we investigated the thermal history of the IGM at z < 3 with precision comparable to the higher redshift results. We find that the temperature of the cosmic gas traced by the Lyα forest [T(Δ¯)] increases for increasing overdensity from T(Δ¯)∼22670 to 33740 K in the redshift range z ∼ 2.8–1.6. Under the assumption of two reasonable values for γ, the temperature at the mean density (T0) shows a tendency to flatten at z ≲ 2.8. In the case of γ ∼ 1.5, our results are consistent with previous ones which indicate a falling T0 for redshifts z ≲ 2.8. Finally, our T(Δ¯) values show reasonable agreement with moderate blazar heating models.